Effects of chronic high fat diet on mediobasal hypothalamic satiety neuron function in POMC-Cre mice - Özge Başer; Yavuz Yavuz; Deniz Öykü Özen; Hüseyin Buğra Özgün; Sami Ağuş; Cihan Civan Civaş; Deniz Atasoy; Bayram Yılmaz (Molecular Metabolism, 2024)
Objective: The prevalence of obesity has increased over the past three decades. Proopiomelanocortin (POMC) neurons in the hypothalamic arcuate nucleus (ARC) play a vital role in induction of satiety. Chronic consumption of high-fat diet is known to reduce hypothalamic neuronal sensitivity to hormones like leptin, thus contributing to the development and persistence of obesity. The functional and morphological effects of a high-calorie diet on POMC neurons and how these effects contribute to the development and maintenance of the obese phenotype are not fully understood. For this purpose, POMC-Cre transgenic mice model was exposed to high-fat diet (HFD) and at the end of a 3- and 6-month period, electrophysiological and morphological changes, and the role of POMC neurons in homeostatic nutrition and their response to leptin were thoroughly investigated. Methods: Effects of HFD on POMC-satiety neurons in transgenic mice models exposed to chronic high-fat diet were investigated using electrophysiological (patch-clamp), chemogenetic and Cre recombinase advanced technological methods. Leptin, glucose and lipid profiles were determined and analyzed. Results: In mice exposed to a high-fat diet for 6 months, no significant changes in POMC dendritic spine number or projection density from POMC neurons to the paraventricular hypothalamus (PVN), lateral hypothalamus (LH), and bed nucleus stria terminalis (BNST) were observed. It was revealed that leptin hormone did not change the electrophysiological activities of POMC neurons in mice fed with HFD for 6 months. In addition, chemogenetic stimulation of POMC neurons increased HFD consumption. In the 3-month HFD-fed group, POMC activation induced an orexigenic response in mice, whereas switching to a standard diet was found to abolish orexigenic behavior in POMC mice. Conclusions: Chronic high fat consumption disrupts the regulation of POMC neuron activation by leptin. Altered POMC neuron activation abolished the neuron's characteristic behavioral anorexigenic response. Change in nutritional content contributes to the reorganization of developing maladaptations.